Peningkatan Kreativitas Mengajar Speaking Skills bagi Guru Bahasa Inggris: Pengabdian - Ilyas, Hamzah Puadi; Ahmad, Zuhad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This training aims to enhance the creativity of English language teachers in teaching speaking skills through approaches based on Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT), as well as the utilization of available technology. The activity was conducted over two days with lectures, discussions, and hands-on practice sessions. The first day focused on theory and discussions regarding creative and relevant speaking teaching techniques, while the second day provided participants with the opportunity to practice the speaking activities they had designed. The results of the training showed a significant improvement in teachers' creativity in designing more varied and engaging speaking activities. Participants also realized that creativity in teaching does not always depend on advanced technology but can be maximized by utilizing available resources in the school environment. Additionally, they gained important insights on how to overcome resource limitations with creative ideas that can be applied in their classrooms. However, some challenges were identified, particularly in the application of technology and the adaptation of new methods in diverse classroom contexts. This training is expected to contribute to the development of more creative and effective English language teaching.